"Are You Authorized to Work in the U.S.?" Investigating "Inclusive" Practices in Rhetoric and Technical Communication Job Descriptions. Issue 2 (3rd April 2021) - Walwema, Josephine; Arzu Carmichael, Felicita
ABSTRACT: This paper studies the language of job descriptions in rhetoric and technical and professional communication to explore how this language might be exclusionary of international scholars. Through critical discourse analysis, we reviewed current U.S. labor and immigration laws and contrasted those laws with the language of hiring documents. We found that hiring documents do not always align with U.S. labor and immigration laws and consequently hinder the hiring prospects of international scholars.